FACTORS CONTRIBUTING TO THE PREVALENCE OF MALARIA AMONG CHILDREN UNDER FIVE YEARS OF AGE ATTENDING HEALTH CARE AT KATABI HEALTH CENTRE III, ENTEBBE MUNICIPALITY. A CROSS-SECTIONAL STUDY. - Ayebale, Kugonza Christine; Mpamize, Habert; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student's Journal of Health Research Africa, 2025)
Background. Malaria is an urgent health priority; its treatment traps families in a cycle of illness, suffering, and poverty. This study aimed to assess the factors contributing to the prevalence of malaria among children under five years attending health care at Katabi Health Center III, Entebbe municipality. Methodology. A quantitative cross-sectional survey design was used, and semi-structured questionnaires were employed with statistical logistics to identify factors associated with the prevalence of malaria among children under five years. Results 92(61.3%) were Females, 37.3% of the participants were 25-34 years, 71(47.3%) were married, and 40% (60/150) of children tested positive for malaria. Statistically, caregivers with low education level (x2=13.405, p=0.004), religion (x2=9.963, p=0.019), drainage system (x2=9.040,p=0.003), cleared bush around homes (x2=4.714,p=0.029), staying close/far from swamp (x2=9.886, p=0.002) and altitude (x2=13.504, p=0.0002) had statistical significance in association with malaria prevalence. But also, caregivers who didn’t take their children to the health facility when sick (x2=10.155, p=0.017) and household factors like type of house (x2=11.866, p=0.003), preventive measures for mosquito bites (x2=10.155, p=0.017) and source of light used played a significant association with malaria prevalence in the under-fives. Conclusion. The Prevalence of malaria was high, and this was influenced by the level of education, religion, drainage system at home, bush around homes, and closeness to the swamp. Recommendation. The Ministry of Health should facilitate more studies in different areas on malaria prevalence, health education to caregivers, municipal administrators organizing meetings with plot owners, and government to reduce electricity generation costs in people’s homes to increase lighting.